COMPONENTS, CRITERIA AND INDICATORS OF PSYCHOLOGICAL READINESS OF TANK UNITS SOLDIERS - Olga Yurkova (Scientific Journal of Polonia University, 2022)
The article deals with an empirical study of the components and theoretical substantiation of indicators and criteria of psychological readiness of tank units soldiers to execute combat tasks and missions. It is determined that the psychological readiness of a tanker is an independent, multifunctional psychological formation, which has a stable positive correlation with the effectiveness to execute a mission; consists of a number of components that interact with each other; is shaped in the process of undergoing a professional training course by a soldier. Applying the method of expert assessments, we have identified and scientifically substantiated that psychological readiness consists of motivational, emotional-volitional, personal and functional components. They were ranked according to their significance. The content of these components is disclosed in criteria that are identical in name. In turn, the criteria are shaped from a number of indicators that reflect the psychological, emotional, and cognitive specificity of the psychological readiness of tank units. Substantiated indicators and criteria allowed us to choose a psychodiagnostic tool for a comprehensive study of the phenomenon of psychological readiness of soldiers of tank units to perform combat missions. Given the complexity of the subject of research, the requirement for psychodiagnostic tools is the partial overlap and complementarity of one method to another and the possibility of their use without separation of the subjects from military service.